SIX-STEP INVERTER UNTUK MENGENDALIKAN MOTOR 3 FASA ARUS SEARAH TANPA SIKAT BERBASIS ARDUINO - Mamal Daputra; Zulwisli Zulwisli (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This research is motivated by the many needs in the use of electric motors. Electric motors with DC voltages that are often used today are less effective and efficient because of the use of brushes that will run out when used. To overcome the weaknesses of this DC motor, then used Brushless Direct current Motor (MASTS). MASTS is a three phase AC motor. In a fixed application, a three phase AC voltage source can be used directly. In a mobile application, it takes an AC voltage sourced from a DC voltage. For this reason, an inverter is designed to convert DC voltage into three phase AC. The method in controlling MASTS is a six-step inverter that is changing the DC voltage to AC voltage in the form of a box or trapezoid. This inverter uses MOSFET IRF3205 and Arduino microcontroller. To find out the performance of the inverter, MOSFET driver voltage measurements, measurement of the output current, and measurement of the resulting MASTS speed. From the measurement results, when the voltage is increased the current in the circuit and the speed of the MASTS will increase. Keywords: Inverter, MASTS, Phase, Six-Step.